The Influence of Release Modifier Differences in Formulations on the Pharmacokinetic Profile of Ketoprofen in Rats: A Scoping Review - Adi Yugatama; Alyanis Mufid SWM; Rasmaya Niruri; Ya-Lin Huang; Nguyen Dang Khoa (Universitas Sebelas Maret, 2024)
The pharmacokinetic profile of drugs can be changed by genetic, environmental, and physiological variables such as age, sex, pregnancy, and different preparations and formulations. Ketoprofen is widely used in many different preparations and formulations. The various formulations can made by adding solubilizing and extending release agents. This study aimed to determine the influence of formulation differences on the pharmacokinetic profile of ketoprofen in rats. This research was a Literature Review. Articles were retrieved from the ScienceDirect and PubMed databases from 2011 to 2020. The inclusion criteria were the research article, the presence of ketoprofen was formulated with the addition of a solubilizing or extended-release agent, given orally and available in open access. The study resulted in differences in formulation, notably the addition of various dissolving agents or extended-release agents, which caused changes in the pharmacokinetic profile of ketoprofen. The highest increase in the pharmacokinetic parameters Cmax and AUC of ketoprofen was observed with poloxamer-188 as a release modifier agent. Therefore, the use of release modifier agents could have a significant effect on the drug's pharmacokinetic profile.